Pengaruh Lingkungan Keluarga, Karakteristik Wirausaha dan Inovasi Produk Terhadap Keberhasilan Usaha - Dahmiri Dahmiri; Idham Khalik (Universitas Batanghari Jambi, 2023)
Micro, Small and Medium Enterprises have a very large role in overcoming unemployment and at the same time can be a solution in alleviating poverty and increasing people's welfare. The problems faced by many MSMEs in achieving business success are related to the family environment, entrepreneurial characteristics and innovation capabilities. This quantitative study aims to analyze the effect of family environment variables, entrepreneurial characteristics and innovation on the success of micro, small and medium enterprises, especially those engaged in culinary businesses in Jambi City. The research population is all culinary business actors in Jambi City while the sample is 100 people. The data were analyzed by multiple linear analysis using the SPSS application. The results of the study conclude that the family environment, entrepreneurial characteristics and innovation have a positive and significant effect both simultaneously and partially on the success of culinary Micro, Small and Medium Enterprises (MSMEs) in Jambi City.